Anisotropic electromechanical properties of GaN ceramics caused by polarisation - Qin, G.S.; Lu, Chunsheng; Umair, M.; Zhao, M.H. (ELSEVIER SCI LTD, 2020)
Based on three-point bending tests and finite element modelling, effects of polarisation directions are investigated on the mechanical and electrical properties of GaN piezoelectric semiconductor ceramics (PSCs). It is shown that polarisation leads to anisotropic electromechanical properties of PSCs. For GaN samples polarised along the vertical direction, their conductive capabilities enhance by nearly 50%, and however, there are almost no changes in ones with horizontal polarisation. Bending strengths of samples with vertical polarisation increase by 11.6% because piezoelectric charges are driven along the polarisation direction under mechanical loading. It is the correlation between mobility and polarisation direction that largely affects the fracture toughness of GaN PSCs. These experimental findings indicate that, in contrast to traditional ceramics, the electromechanical properties of GaN ceramics can be tailored through polarisation directions.